Effect of activated carbon in Polysufone-Polyethyleneimine-Silver composite membrane towards adsorption of chromium (Cr), lead (Pb), silver (Ag) and cadmium (Cd) in synthetic wastewater - Mohamad Said, K. A.; Genevieve Gadung, George; Mohamed Alipah, N. A.; Nor Zakirah, Ismail; Ramizah Liyana, Jama'In; Norlisa, Mili (Universite Mohammed Premier Oujda, 2017)
Adsorption of heavy metal has been monopoly by activated carbon either in solid or powder form and the introduction of membrane consist of activated carbon could therefore increase the capacity of adsorption. The objective of this work was to investigate the effect of adding activated carbon in a Polysufone-Polyethyleneimine-Silver (Psf-PEI-Ag) composite membrane in terms of the heavy metal adsorption in synthetic wastewater. The membrane was developed by phase inversion at different composition of activated carbon (from 0 to 0.9%) while the other components were kept constant at 15% Psf, 0.5% Ag and 0.3% PEI. The SEM image showed a symmetrical membrane matrix with sponge-like structure. The composite membrane with 0.9wt% AC has the highest water flux and removal of heavy metal (chromium, lead, silver and cadmium). The percentage of heavy metal reduction by the composite membrane was 35% cadmium, 19% chromium, 16% silver and 2% lead. The result indicated that the introduction of activated carbon indeed plays an important role towards enhancing the adsorption of heavy metal. This work is expected to provide better understanding of activated carbon in PEI-Ag membrane and to inspire new approaches in designing membrane with higherheavy metal removal. © 2017 University of Mohammed Premier Oujda Morocco.